Seaweed grown on low-value residual streams and its potential use in a safe circular food system - G.W. Spaans; M.C. Keur; E.M. Foekema; W. Muizelaar; R.W. Nauta; K. Niermans; J.L. Banach (Applied Food Research)
There is an urgent need to shift our food systems from linear to circular to enhance efficient nutrient use. This can be achieved by valorizing low-value residual streams to high, added-value products like fertilizers or nutrient sources for animal feed. This study aimed (i) to assess if sewage sludge (STP-city) and potato industry sludge (FTP-potato) could be used to cultivate seaweed (Ulva spp.) and (ii) to determine the potential for the residual streams and seaweed in safe circular food production systems. Our results showed that the seaweed could grow on STP-city and FTP-potato sludges when sufficient inorganic nitrogen was included. DNA of Bacillus spp., Campylobacter spp., and Vibrio spp. were detected in the sludges and sludge-grown seaweed. For sludge-grown seaweed, heavy metal and elemental concentrations did not exceed the European Union (EU) maximum limits for feed materials. Results also give insight into per- and polyfluoroalkyl substances (PFASs) in sludge-grown seaweed. Future efforts should be directed towards providing appropriate nutrient ratios for the seaweed and determining suitable food-safe, risk-based pre-treatments for sludge and seaweed before entry into the food system. When food safety is considered, a first step is taken towards incorporating sludge and seaweed in safe, circular food production systems.